Struktur Dan Fungsi Cerita Legenda Mbah Wungu Bagi Masyarakat Desa Kwaron Kecamatan Diwek Kabupaten Jombang - Banu Wicaksono; Elly Ainur Rosyidah (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study intends to investigate the narrative structure and social functions of the Mbah Wungu Legend from Kwaron Village, Diwek Subdistrict, Jombang Regency. The research employs a qualitative approach with the narrative structure theory perspective proposed by Maranda. The research object is the oral story of the Mbah Wungu Legend, while data sources include village officials, community leaders, the caretaker of the sacred site (punden), and residents living near the research location. Data were gathered through observation, audio-visual recording, written notes, and interviews, transcription, translation, and analysis based on narrative structure theory and social function. The findings indicate that the narrative structure of the Mbah Wungu Legend is coherent, comprising the terem elements (magical figures, natural phenomena, historical context, and personal dramatization) and functional elements that convey positive values. The figure of Mbah Wungu is depicted as a spiritual-maternal figure and the village danyang, serving as a community protector, leader in land-clearing activities, and a moral guide emphasizing mindful speech, patience, and harmonious living. The social functions of the legend include serving as a tool for community education, strengthening solidarity, regulating behavior, providing a medium for social critique, offering an escape from reality, and transforming labor into enjoyable activity. Moreover, the legend reinforces collective identity through the annual cultural preservation tradition at Punden Mbah Wungu and conveys ecological messages, particularly regarding respect for nature, symbolized by sacred purple-flowering trees. The study implies that the Mbah Wungu Legend serves not only as a source of entertainment but also as a vehicle for internalizing moral, social, spiritual, and ecological values, strengthening collective memory and local cultural identity. These findings are expected to contribute to the preservation of Indonesian oral folklore through a multidisciplinary approach while inspiring younger generations to maintain both tradition and ecological guardianship.